The Role of Parents and Its Significance in Forming a Healthy Lifestyle in the Family - Robilova Sharofatkhon (Genius Journals, 2022)
In this article, parents are given the necessary advice to direct the life of their children in the right direction and organize a healthy lifestyle. When parents are at home, they are advised to make a schedule in accordance with the schedule in kindergarten or school, depending on the age of the children. The daily routine is important not only for children, but also for adults. Therefore, it is recommended to follow the advice of teachers and pediatricians when planning a children's day
Keywords: Adequate; assimilation; healthy lifestyle; regime